A Modified Version of Round Robin Algorithm “Modulo Based Round Robin Algorithm” - Ankush Joshi, S. B. Goyal, Kalpana Sharma (International Journal of Advanced Science and Technology, 2020)
Process scheduling is a very important task of Multiprogramming operating system[1]. Multiprogramming operating system allows a single time unit to enter n number of processes into the executable memory and these n numbers of processes share the CPU. At this stage process scheduler manages the processes according to various process scheduling algorithms such as- FCFS, SJF, SRTF, Round robin etc. In this paper we propose a new variant of round robin algorithm which is called “Modulo Based Round Robin Algorithm”. In this proposed algorithm by applying some mathematical calculation we assign priority to the processes and after that assign the processes to the processor according to round robin algorithm. Simply we can say that new proposed algorithm inherits the properties of round robin as well as priority scheduling algorithm.